Lithium manganese iron phosphate material as well as preparation method and application thereof

By employing a method for preparing lithium manganese iron phosphate materials with gradient manganese doping, magnesium doping, and carbon coating, the problems of manganese ion dissolution and low conductivity under high temperature conditions were solved, resulting in improved high conductivity and cycle stability of the material.

CN120864537AInactive Publication Date: 2025-10-31HUNAN YUNENG NEW ENERGY BATTERY MATERIALS CO LTD
View PDF 0 Cites 1 Cited by

Patent Information

Application Number
CN202511363002.1
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-09-23
Publication Date
2025-10-31
Estimated Expiration
Not applicable · inactive patent

AI Technical Summary

Technical Problem

In lithium manganese iron phosphate materials, manganese ions are easily dissolved at high temperatures, which affects cycle life, and the conductivity is low, which needs to be improved by coating with a conductive layer.

Method used

A gradient manganese-doped core, magnesium-doped layer, carbon coating layer, and Al2O3 coating layer were used to prepare the material. By adding MnSO4 solution of different concentrations in stages, a manganese ion concentration gradient was formed. Combined with the stability of magnesium ions and the conductivity of carbon nanotubes, a stable material structure was formed.

Benefits of technology

It significantly improves the electrical conductivity and cycle stability of the material, reduces the dissolution of manganese ions under high temperature conditions, and enhances the charge-discharge performance and structural stability of the material.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
Patent Text Reader

Abstract

The invention provides a lithium manganese iron phosphate material and a preparation method and application thereof, and belongs to the technical field of lithium batteries, the lithium manganese iron phosphate material comprises a gradient manganese-doped core, a magnesium-doped layer, a carbon coating layer and an Al2O3 coating layer; the gradient manganese-doped inner core sequentially comprises a manganese-containing core layer, a manganese-containing transition layer and a manganese-containing shell from inside to outside, and the manganese ion concentration of the manganese-containing core layer is from high to low. According to the lithium manganese iron phosphate material disclosed by the invention, the gradient manganese-doped core is designed, so that the concentration gradient distribution of manganese ions is realized, and the electrochemical performance of the material is optimized. Meanwhile, due to the introduction of the magnesium doping layer, the cycling stability and the thermal stability of the material are further improved, and the manganese ion dissolution phenomenon in a high-temperature environment is reduced; in addition, the use of the carbon coating layer significantly improves the conductivity of the material and improves the charge and discharge performance of the material, and the Al2O3 coating layer can improve the structural stability of the material and reduce the dissolution of manganese ions, and also can improve the cycling stability and thermal stability of the material.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This application relates to the field of lithium battery technology, and in particular to a lithium manganese iron phosphate material, its preparation method and application. Background Technology

[0002] Lithium manganese iron phosphate (LMFP) is a cathode material formed by doping manganese on lithium iron phosphate (LFP). It has both high safety and high energy density characteristics and is regarded as the core direction of the next generation of lithium-ion battery technology.

[0003] LMFP inherits the olivine crystal structure of LFP, has stable chemical properties, suppresses the risk of thermal runaway, and has better safety than ternary materials; its working voltage platform is increased to 4.1V (LFP is 3.4V), and its energy density can reach 230 Wh / kg, which is 15%-20% higher than LFP.

[0004] Lithium manganese iron phosphate (LFP) improves voltage through manganese doping, and its energy density is close to that of ternary 523 / 622. LFP retains about 71% capacity at -20℃, which can be increased to 74% after mixing with ternary materials, which is better than LFP's 67%. Moreover, manganese ore resources are abundant, and the raw material cost is close to that of LFP, but the complexity of the production process leads to a slightly higher overall cost of 5%-10%.

[0005] Lithium manganese iron phosphate (LFP) has a lower conductivity than lithium manganese iron phosphate (LFP), which needs to be improved by coating with a conductive layer. Furthermore, manganese ions are easily dissolved at high temperatures, affecting cycle life. Therefore, it is necessary to improve existing LFP materials to reduce manganese ion dissolution at high temperatures. Summary of the Invention

[0006] This application is made in view of the above-mentioned problems, and its purpose is to provide a lithium manganese iron phosphate material, its preparation method and application.

[0007] Specifically, the first aspect of this application provides a method for preparing lithium manganese iron phosphate material, comprising the following steps: S1: Add a first concentration of MnSO4 solution to the iron source suspension to generate a manganese core layer; continue to add a second concentration of MnSO4 solution to the reaction system to generate a manganese transition layer; continue to add a third concentration of MnSO4 solution to the reaction system to generate a manganese shell, thereby obtaining a gradient manganese-doped core. S2: Add Mg(NO3)2 solution to the gradient manganese doped core, ultrasonically react to form a magnesium doped layer, wash and spray dry to obtain precursor powder; S3: Mix the precursor powder with the carbon source to form uniformly coated composite particles, sinter the composite particles, cool and then pulverize to obtain lithium manganese iron phosphate powder. S4: Mix nano-alumina with lithium manganese iron phosphate powder, calcine to generate an Al2O3 coating layer, and obtain lithium manganese iron phosphate material.

[0008] Furthermore, the iron source suspension is prepared by dispersing FePO4·2H2O in deionized water, adding phosphoric acid to adjust the pH to 2-3, and forming a FePO4 suspension.

[0009] Furthermore, in the first concentration of MnSO4 solution and the iron source suspension, the molar ratio of Mn to Fe is 0.6-0.7:0.3-0.4; In the second concentration of MnSO4 solution and the iron source suspension, the molar ratio of Mn to Fe is 0.5-0.6:0.4-0.5; In the third concentration MnSO4 solution and the iron source suspension, the molar ratio of Mn to Fe is 0.4-0.5:0.5-0.6.

[0010] Furthermore, the reaction temperature for generating the manganese-containing core layer in step S1 is 55-65℃, and the reaction time is 1.5-2.5h; The reaction temperature for generating the manganese-containing transition layer is 65-75℃, and the reaction time is 1-2h. The reaction temperature for generating the manganese-containing shell is 75-85℃, and the reaction time is 0.5-1.5h.

[0011] Furthermore, the Mg in the Mg(NO3)2 solution in step S2 2+ The molar amount is 2-5% of the total molar amount of metal in the gradient manganese doped core reaction system.

[0012] Furthermore, the carbon source in step S3 is prepared by ball milling carbonized biomass carbon and mixing it with carbon nanotubes at a mass ratio of 2.5-3.5:1.

[0013] Furthermore, the sintering described in step S3 is microwave-assisted sintering under a protective atmosphere, with a microwave power of 4-5.5 kW, including: Increase the temperature to 450-500℃ at a rate of 8-10℃ / min and hold for 1-1.5 hours; Then, increase the temperature to 700-750℃ at a rate of 15-20℃ / min and microwave irradiate for 30-40min. After cooling in the furnace to below 200°C, remove it from the furnace.

[0014] Furthermore, the calcination described in step S4 is calcination at 600-650℃ for 2.5-3 hours under a protective atmosphere.

[0015] A second aspect of this application provides a lithium manganese iron phosphate material, comprising a gradient manganese doped core, a magnesium doped layer, a carbon coating layer, and an Al2O3 coating layer; The gradient manganese doped core consists of a manganese-containing core layer, a manganese-containing transition layer, and a manganese-containing outer shell, with manganese ion concentration decreasing from the inside out.

[0016] The third aspect of this application provides the application of the lithium manganese iron phosphate material described above, or the lithium manganese iron phosphate material prepared by the preparation method of the lithium manganese iron phosphate material, in the cathode material of lithium batteries.

[0017] The present invention has the following beneficial effects: The method for preparing lithium manganese iron phosphate material of this invention involves designing a gradient manganese-doped core. By adding MnSO4 solution of different concentrations in stages, a concentration gradient distribution of manganese ions is achieved. This unique core structure makes the ion migration inside the material more orderly, thereby optimizing the electrochemical performance of the material. Precise control of the temperature and time of each layer reaction is crucial in the preparation of the gradient manganese-doped core. A suitable temperature and time range ensures the uniformity and stability of each layer structure, laying the foundation for subsequent material performance improvement. In the reaction system containing the gradient manganese-doped core, Mg(NO3)2 solution is added in a specific ratio to form a magnesium-doped layer. The presence of magnesium ions can effectively suppress the dissolution of manganese ions under high-temperature conditions. Magnesium ions can form stable chemical bonds with other components in the material, enhancing the structural stability of the material, reducing the dissolution channels of manganese ions, and thus significantly improving the cycling stability and thermal stability of the material. Carbonized biomass carbon, after ball milling, is mixed with carbon nanotubes in a specific mass ratio as a carbon source. This composite carbon source can uniformly coat the material surface. Carbon nanotubes possess excellent electrical conductivity and a high aspect ratio, enabling them to form a conductive network on the material surface. Carbonized biomass carbon provides abundant porosity, facilitating lithium-ion diffusion. The synergistic effect of these two materials significantly improves the material's electrical conductivity and charge-discharge performance. The formation of an Al2O3 coating further enhances the material's performance. By mixing nano-alumina with lithium manganese iron phosphate powder and calcining it at a specific temperature under a protective atmosphere, an Al2O3 coating is generated. Al2O3 exhibits good chemical stability and mechanical properties, forming a dense protective film on the material surface to prevent manganese ion dissolution and improve the material's structural stability. Furthermore, the Al2O3 coating also improves the material's cycle stability and thermal stability, allowing it to maintain good performance under various operating environments.

[0018] The lithium manganese iron phosphate material of this invention achieves a gradient distribution of manganese ion concentration by designing a gradient manganese doped core, thereby optimizing the electrochemical performance of the material. The manganese-containing core layer, manganese-containing transition layer, and manganese-containing shell structure of the gradient manganese doped core not only improve the utilization rate of manganese ions but also enhance the structural stability of the material. By reducing the surface manganese content through gradient doping, the Mn content in the electrolyte after cycling is reduced. 2+The concentration is <6ppm; at the same time, the introduction of magnesium doping layer further improves the cycling stability and thermal stability of the material and reduces the dissolution of manganese ions under high temperature environment; in addition, the use of carbon coating layer significantly improves the conductivity of the material and improves the charge and discharge performance of the material, with a capacity retention of >86% after 100 cycles at 1C; Al2O3 coating layer can improve the structural stability of the material, reduce the dissolution of manganese ions, and also improve the cycling stability and thermal stability of the material.

[0019] Applying the lithium manganese iron phosphate material of this invention to lithium battery cathode materials can significantly improve the energy density, cycle stability, and safety of lithium batteries. Compared with existing technologies, the lithium manganese iron phosphate material of this invention achieves a significant increase in energy density while maintaining high safety, and has broad application prospects. Detailed Implementation

[0020] To make the objectives, technical solutions, and advantages of this application clearer, the following description and illustration are provided in conjunction with embodiments. It should be understood that the specific embodiments described herein are merely illustrative and not intended to limit the scope of this application. All other embodiments obtained by those skilled in the art based on the embodiments provided in this application without inventive effort are within the scope of protection of this application.

[0021] Obviously, the following description is merely some examples or embodiments of this application. Those skilled in the art can apply this application to other similar scenarios without any inventive effort. Furthermore, it is understood that although the effort involved in such development may be complex and lengthy, for those skilled in the art related to the content disclosed in this application, any changes to design, manufacturing, or production based on the technical content disclosed in this application are merely conventional technical means and should not be construed as insufficient disclosure of the content of this application.

[0022] Unless otherwise specified, the terms "comprising" and "including" as used in this application can be open-ended or closed-ended. For example, "comprising" and "including" can mean that other components not listed may also be included, or that only the listed components may be included.

[0023] Unless otherwise specified, the term "or" is inclusive in this application. For example, the phrase "A or B" means "A, B, or both A and B". More specifically, the condition "A or B" is satisfied by any of the following conditions: A is true (or exists) and B is false (or does not exist); A is false (or does not exist) and B is true (or exists); or both A and B are true (or exist).

[0024] An embodiment of the first aspect of this application provides a method for preparing lithium manganese iron phosphate material, comprising the following steps: S1: Add a first concentration of MnSO4 solution to the iron source suspension to generate a manganese core layer; continue to add a second concentration of MnSO4 solution to the reaction system to generate a manganese transition layer; continue to add a third concentration of MnSO4 solution to the reaction system to generate a manganese shell, thereby obtaining a gradient manganese-doped core. S2: Add Mg(NO3)2 solution to the gradient manganese doped core, ultrasonically react to form a magnesium doped layer, wash and spray dry to obtain precursor powder; S3: Mix the precursor powder with the carbon source to form uniformly coated composite particles, sinter the composite particles, cool and then pulverize to obtain lithium manganese iron phosphate powder. S4: Mix nano-alumina with lithium manganese iron phosphate powder, spray dry, and calcine to generate an Al2O3 coating layer to obtain lithium manganese iron phosphate material.

[0025] Specifically, the iron source suspension is formed by dispersing FePO4·2H2O in deionized water at a solid-liquid ratio of 1:10, and adding phosphoric acid to adjust the pH to 2-3.

[0026] The MnSO4 solution was divided into three gradients: high manganese, medium manganese, and low manganese, with concentrations of 1.5 mol / L, 1.0 mol / L, and 0.5 mol / L, respectively.

[0027] A gradient precipitation reaction was carried out under nitrogen protection: a high-concentration MnSO4 solution was added dropwise to a FePO4 suspension, wherein the molar ratio of Mn to Fe in the first concentration (high concentration) MnSO4 solution and the iron source suspension was 0.6-0.7:0.3-0.4; NH3·H2O was added simultaneously to adjust the pH to 4-5, and the reaction was stirred at 55-65℃ for 1.5-2.5 h to generate a precursor containing a manganese core layer. Maintain the pH at 4-5, add a medium-concentration MnSO4 solution dropwise. The molar ratio of Mn to Fe in the second concentration (medium concentration) MnSO4 solution and the iron source suspension is 0.5-0.6:0.4-0.5. React at 65-75℃ for 1-2 hours to generate a manganese-containing transition layer. A low-concentration MnSO4 solution was used instead. In the iron source suspension, the molar ratio of Mn to Fe in the third concentration (low concentration) MnSO4 solution was 0.4-0.5:0.5-0.6. The reaction was carried out at 75-85℃ for 0.5-1.5h to complete the gradient structure coating.

[0028] In this embodiment, Mg(NO3)2 solution was slowly added to the reaction system with ultrasonic assistance (40 kHz × 1 h) to allow Mg to react. 2+ It is uniformly adsorbed onto the surface of the precursor.

[0029] Specifically, the Mg in the Mg(NO3)2 solution in step S2 2+ The molar amount is 2-5% of the total metal molar amount in the gradient manganese doped core reaction system.

[0030] The reaction product containing the magnesium doped layer was washed three times by alternating centrifugation with deionized water and ethanol at 8000 rpm for 10 min each time to remove residual ions. During spray drying, the inlet temperature was 180℃ and the outlet temperature was 90℃ to obtain microspherical gradient doped precursor powder with a particle size of 3-5 μm.

[0031] In this embodiment, the carbon source prepared in step S3 is prepared by ball milling carbonized biomass carbon (zirconia balls, 400 rpm, 4 h) and then mixing it with carbon nanotubes at a mass ratio of 2.5-3.5:1, using ethanol as a medium, and ultrasonically dispersing for 1 h. The biomass carbon is rice husk, bamboo charcoal, etc.

[0032] The precursor powder and 5 wt% of the composite carbon source were premixed in a high-speed mixer at 2000 rpm for 30 min. Then, 0.8 wt% of titanate coupling agent was added and the mixture was continued for 1 h to form uniformly coated composite particles.

[0033] The sintering of the composite particles in step S3 is carried out under a protective atmosphere (nitrogen atmosphere) using microwave-assisted sintering with a microwave power of 4-5.5 kW, including: The temperature is increased to 450-500℃ at a rate of 8-10℃ / min and held for 1-1.5 hours to decompose organic matter and form initial crystal nuclei. Then, the temperature is increased to 700-750℃ at a rate of 15-20℃ / min, and microwave irradiation is performed for 30-40 min to promote the Li... + Diffusion and lattice rearrangement inhibit manganese migration; Remove the product after it has cooled to below 200°C in the furnace to avoid cracking caused by rapid cooling.

[0034] The sintered material was then subjected to air jet milling at a pressure of 0.8 MPa until the particle size was 1.5-2 μm, resulting in uniform lithium manganese iron phosphate powder.

[0035] In this embodiment, step S4 involves mixing lithium manganese iron phosphate powder with nano-alumina dispersion, ball milling at 400 rpm, and using a zirconia ball to material ratio of 5:1. Then, spray drying is performed at an inlet temperature of 200°C and an outlet temperature of 90°C to obtain LMFP / Al2O3 composite powder.

[0036] The LMFP / Al2O3 composite powder is calcined in a nitrogen atmosphere at 600-650℃ for 2.5-3 hours to form an Al2O3 coating layer.

[0037] The second aspect of this application provides a lithium manganese iron phosphate material, comprising a gradient manganese doped core, a magnesium doped layer, a carbon coating layer, and an Al2O3 coating layer; The gradient manganese doped core consists of a manganese-containing core layer, a manganese-containing transition layer, and a manganese-containing outer shell, with manganese ion concentration decreasing from the inside out.

[0038] The lithium manganese iron phosphate material of this invention achieves a gradient distribution of manganese ion concentration by designing a gradient manganese doped core, thereby optimizing the electrochemical performance of the material. The manganese-containing core layer, manganese-containing transition layer, and manganese-containing shell structure of the gradient manganese doped core not only improve the utilization rate of manganese ions but also enhance the structural stability of the material. Gradient doping reduces the surface manganese content, thus reducing manganese dissolution. Simultaneously, the introduction of a magnesium doped layer further improves the cycling stability and thermal stability of the material, reducing manganese ion dissolution at high temperatures. Furthermore, the use of a carbon coating layer significantly improves the electrical conductivity of the material, enhancing its charge-discharge performance. An Al2O3 coating layer can improve the structural stability of the material, reduce manganese ion dissolution, and also improve the cycling stability and thermal stability.

[0039] The third aspect of this application provides an application of the lithium manganese iron phosphate material described above, or the lithium manganese iron phosphate material prepared by the preparation method of the lithium manganese iron phosphate material, in the cathode material of a lithium battery.

[0040] Example 1 A method for preparing lithium manganese iron phosphate material includes the following steps: S1: Disperse FePO4·2H2O in deionized water at a solid-liquid ratio of 1:10, add phosphoric acid to adjust the pH to 2.5, and form a FePO4 suspension; add 1.5 mol / L MnSO4 solution to the FePO4 suspension, with a molar ratio of Mn to Fe of 0.65:0.35, and simultaneously add NH3·H2O to adjust the pH to 4.5. Stir the reaction at 60℃ for 2 hours to generate a manganese core layer. Maintaining the pH at 4.5, continue adding 1.0 mol / L MnSO4 solution to the reaction system, with a molar ratio of Mn to Fe of 0.55:0.45; react at 70℃ for 1.5 h, and a manganese-containing transition layer is formed. Add 0.5 mol / L MnSO4 solution to the reaction system, with a molar ratio of Mn to Fe of 0.45:0.55, and react at 80℃ for 1 h. The reaction produces a manganese-containing outer shell, thus obtaining a gradient manganese-doped core. S2: Add Mg(NO3)2 solution to the gradient manganese doped core, sonicate at 40kHz for 1h to form a magnesium doped layer. Wash the reaction product containing the magnesium doped layer with deionized water and ethanol three times by alternating centrifugation at 8000rpm for 10min each time to remove residual ions. Spray dry at an inlet temperature of 180℃ and an outlet temperature of 90℃ to obtain microspherical gradient doped precursor powder with a particle size of 3-5μm. S3: Carbonized rice husks were ball-milled and then mixed with carbon nanotubes at a mass ratio of 3.2:1. The mixture was ultrasonically dispersed for 1 hour using ethanol as the medium to obtain a carbon source. The precursor powder was mixed with the carbon source and premixed in a high-speed mixer at 2000 rpm for 30 minutes. 0.8 wt% titanate coupling agent was added, and mixing continued for 1 hour to form uniformly coated composite particles. The composite particles were then subjected to microwave-assisted sintering in a nitrogen atmosphere at a microwave power of 5 kW. Specifically: The temperature was increased to 450℃ at 8℃ / min and held for 1 hour; then the temperature was increased to 700℃ at 15℃ / min and microwave irradiated for 30 minutes. Remove from the furnace after cooling to below 200°C to avoid cracking caused by rapid cooling. After cooling, lithium iron phosphate powder was obtained by air jet milling. S4: Mix nano-alumina dispersion with lithium manganese iron phosphate powder, spray dry, and calcine at 600℃ for 3h under nitrogen atmosphere to generate an Al2O3 coating layer, thereby obtaining lithium manganese iron phosphate material.

[0041] Example 2 This embodiment is basically the same as Example 1, except that in the reaction to produce the manganese core layer, the molar ratio of Mn to Fe is 0.62:0.38, NH3·H2O is added to adjust the pH to 5, and the reaction is stirred at 65°C for 1.5 h.

[0042] Example 3 This embodiment is basically the same as Example 1, except that in the reaction to generate the manganese-containing transition layer, the molar ratio of Mn to Fe is 0.58:0.42; and the reaction is carried out at 65°C for 2 hours.

[0043] Example 4 This embodiment is basically the same as Example 1, except that in the reaction to generate the manganese-containing shell, the molar ratio of Mn to Fe is 0.49:0.58, and the reaction is carried out at 75°C for 1.5 hours.

[0044] Example 5 This embodiment is basically the same as Embodiment 1, except that in step S3, the carbonized bamboo charcoal is ball-milled and then mixed with carbon nanotubes at a mass ratio of 2.5:1.

[0045] Example 6 This embodiment is basically the same as Embodiment 1, except that in step S3, during microwave-assisted calcination, the temperature is increased to 500°C at 10°C / min and held for 1.5 hours; then the temperature is increased to 750°C at 18°C / min and microwave irradiated for 30 minutes.

[0046] Example 7 This embodiment is basically the same as that of Embodiment 1, except that in step S4, the Al2O3 coating layer is generated by calcination at 650°C for 2.5 h under a nitrogen atmosphere.

[0047] Comparative Example 1 This comparative example is basically the same as Example 1, except that the MnSO4 solution in step S1 is not gradient doped, but uniformly doped.

[0048] Comparative Example 2 This comparative example is basically the same as Example 1, except that in step S3, the biomass char rice husk and carbon nanotubes in the carbon source are mixed and replaced with acetylene black.

[0049] Comparative Example 3 This comparative example is basically the same as Example 1, except that microwave-assisted sintering is not performed in step S4.

[0050] Comparative Example 4 This comparative example is basically the same as Example 1, except that Al2O3 coating is not performed in step S4.

[0051] The lithium manganese iron phosphate materials prepared in Examples 1-7 and Comparative Examples 1-4 were applied to batteries, and their performance was tested. The results are shown in Table 1.

[0052] As shown in the table above, the lithium manganese iron phosphate material with the gradient manganese doped core, magnesium doped layer, carbon coating layer, and Al2O3 coating layer structure provided in this application exhibits higher initial discharge capacity, better cycle stability, and lower manganese ion dissolution compared to traditional uniformly doped materials. The lithium manganese iron phosphate materials of Examples 1 to 7 all showed a capacity retention rate of over 86% after 100 cycles at 1C, and the Mn content after 100 cycles at 1C was also significantly higher. 2+ The dissolution amounts were all below 0.044 mg / kg, demonstrating excellent electrochemical performance and stability.

[0053] In particular, compared with Example 1, Comparative Example 1 did not use gradient doping technology, but instead used uniform doping, which led to a decrease in the initial discharge capacity of the material and a significant decrease in cycle stability. After 100 cycles at 1C, Mn 2+The dissolution rate increased significantly to 0.052 mg / kg. This may be because the present invention uses gradient manganese doping, which reduces the active manganese content at the electrolyte contact surface by a low-manganese layer, thereby reducing oxidation side reactions. The internal high-manganese core layer can provide high capacity contribution and alleviate lattice stress during lithium insertion / extraction through gradient transition, thereby improving the various performance characteristics of the battery. In contrast, the uniform doping in Comparative Example 1 resulted in excessively high local manganese ion concentrations in the material, which easily caused manganese dissolution and structural damage, thus affecting the electrochemical performance and cycle stability of the material.

[0054] In Comparative Example 2, replacing the biomass char rice husk and carbon nanotubes in the carbon source with acetylene black resulted in a decrease in the material's performance. This is because rice husk has a porous carbon structure, and its high specific surface area provides lithium-ion diffusion channels. Furthermore, CNTs act as bridges, connecting carbon particles to form a continuous conductive pathway and reducing interfacial impedance. In contrast, the acetylene black in Comparative Example 2 is a solid carbon sphere with a smaller specific surface area, and it cannot form an effective conductive network, leading to a decrease in the material's electrochemical performance.

[0055] In Comparative Example 3, without microwave-assisted sintering, the material properties were also reduced. Microwave-assisted sintering has advantages such as rapid heating, uniform temperature, and energy efficiency, and can promote the heating of Li... + Diffusion and lattice rearrangement improve the crystallinity and density of materials, thereby enhancing their electrochemical performance. However, the traditional sintering method used in Comparative Example 3 may result in insufficient crystallinity and density, thus affecting the material's electrochemical performance.

[0056] In Comparative Example 4, the material performance was also reduced due to the absence of Al2O3 coating. The Al2O3 coating improves the structural stability of the material, reduces manganese ion dissolution, and also enhances its cycling and thermal stability. However, the lack of Al2O3 coating in Comparative Example 4 resulted in poorer structural stability, increased manganese ion dissolution, and compromised cycling stability.

[0057] In summary, the preparation method of lithium manganese iron phosphate provided in this application, through steps such as gradient manganese doping, magnesium doping, carbon coating, and Al2O3 coating, can produce lithium manganese iron phosphate materials with excellent electrochemical performance and stability. This material has broad application prospects in lithium battery cathode materials and can improve the cycle stability and safety of batteries.

[0058] It should be noted that this application is not limited to the above-described embodiments. The above embodiments are merely examples, and any embodiments with the same structure and effect as the technical concept within the scope of this application are included in the technical scope of this application. Furthermore, various modifications that can be conceived by those skilled in the art to the embodiments, and other ways of constructing by combining some of the constituent elements of the embodiments, without departing from the spirit of this application, are also included in the scope of this application.

Claims

1. A method for preparing lithium manganese iron phosphate material, characterized in that, Includes the following steps: S1: Add a first concentration of MnSO4 solution to the iron source suspension to generate a manganese core layer; continue to add a second concentration of MnSO4 solution to the reaction system to generate a manganese transition layer; continue to add a third concentration of MnSO4 solution to the reaction system to generate a manganese shell, thereby obtaining a gradient manganese-doped core. S2: Add Mg(NO3)2 solution to the gradient manganese doped core, ultrasonically react to form a magnesium doped layer, wash and spray dry to obtain precursor powder; S3: Mix the precursor powder with the carbon source to form uniformly coated composite particles, sinter the composite particles, cool and then pulverize to obtain lithium manganese iron phosphate powder. S4: Mix nano-alumina with lithium manganese iron phosphate powder, calcine to generate an Al2O3 coating layer, and obtain lithium manganese iron phosphate material.

2. The method for preparing lithium manganese iron phosphate material according to claim 1, characterized in that, The iron source suspension is prepared by dispersing FePO4·2H2O in deionized water, adding phosphoric acid to adjust the pH to 2-3, and forming a FePO4 suspension.

3. The method for preparing lithium manganese iron phosphate material according to claim 1, characterized in that, In the first concentration of MnSO4 solution and the iron source suspension, the molar ratio of Mn to Fe is 0.6-0.7:0.3-0.4; In the second concentration of MnSO4 solution and the iron source suspension, the molar ratio of Mn to Fe is 0.5-0.6:0.4-0.5; In the third concentration MnSO4 solution and the iron source suspension, the molar ratio of Mn to Fe is 0.4-0.5:0.5-0.

6.

4. The method for preparing lithium manganese iron phosphate material according to claim 1, characterized in that, The reaction temperature for generating the manganese-containing core layer in step S1 is 55-65℃, and the reaction time is 1.5-2.5h. The reaction temperature for generating the manganese-containing transition layer is 65-75℃, and the reaction time is 1-2h. The reaction temperature for generating the manganese-containing shell is 75-85℃, and the reaction time is 0.5-1.5h.

5. The method for preparing lithium manganese iron phosphate material according to claim 1, characterized in that, Mg in the Mg(NO3)2 solution in step S2 2+ The molar amount is 2-5% of the total metal molar amount in the gradient manganese doped core reaction system.

6. The method for preparing lithium manganese iron phosphate material according to claim 1, characterized in that, The carbon source in step S3 is prepared by ball milling carbonized biomass carbon and mixing it with carbon nanotubes at a mass ratio of 2.5-3.5:

1.

7. The method for preparing lithium manganese iron phosphate material according to claim 1, characterized in that, The sintering described in step S3 is microwave-assisted sintering under a protective atmosphere, with a microwave power of 4-5.5 kW, including: Increase the temperature to 450-500℃ at a rate of 8-10℃ / min and hold for 1-1.5 hours; Then, increase the temperature to 700-750℃ at a rate of 15-20℃ / min and microwave irradiate for 30-40min. After cooling in the furnace to below 200°C, remove it from the furnace.

8. The method for preparing lithium manganese iron phosphate material according to claim 2, characterized in that, The calcination described in step S4 is calcination at 600-650℃ for 2.5-3 hours under a protective atmosphere.

9. A lithium manganese iron phosphate material, characterized in that, The lithium manganese iron phosphate material is prepared by the method according to any one of claims 1-8, wherein the lithium manganese iron phosphate material comprises a gradient manganese doped core, a magnesium doped layer, a carbon coating layer and an Al2O3 coating layer; The gradient manganese doped core consists of a manganese-containing core layer, a manganese-containing transition layer, and a manganese-containing outer shell, with manganese ion concentration decreasing from the inside out.

10. The application of lithium manganese iron phosphate material as described in claim 9 or lithium manganese iron phosphate material prepared by any one of the preparation methods of lithium manganese iron phosphate material according to claims 1-8 in the cathode material of lithium batteries.

Citation Information

Cited By

  • High-nickel positive electrode material coated with organic-inorganic hybrid solid polymer electrolyte and preparation method and application of high-nickel positive electrode material

    CN122051185A